Identification of the presence of human papilloma virus in female patients in Kelantan with cervical cancer using hybridization in situ - Hayati, Nor; Madhavan, Manoharan; Sidek, Mohamad Ros; Jusoh, Rosli (2000)
The aims of this research was to introduce this new technique in Universiti Sains Malaysia pathology laboratory, to study whether those krilocytes seen in tissue sections stained by HIE are HPV infected cells, To study the incidence of HPV, related cervical neoplasia in Kelantan female population. The association of Human Papilloma viral infection with cervical cancer is wen proven. To investigate this association in local population, we carried out testing more than 60 archival cases in department of Pathology, Universiti Sains Malaysia. These cases were identified based on the presence of koilocytcs cytopathic effect noted at light microscopy of the sections of the biopsies stained by the routine staining of Haematoxylin and eosin (HIE).The first phase of the research was testing for the presence of Human Papilloma Virus DNA utilising in situ hybridisation method with wide spectrum HPV DNA probes. These commercial probes are obtained from DAKO. The broad spec1rum probes contain genomic DNA targets specific to HPV type 6, 11, 16, 18, 30, 31, 33, 35, 45, 51 and 52. The HPV types commonly associated with cancer of the cervix is Type 16 and 18. These probes do not act with human nuclear DNA We tested 25 cases, 19 of them was found to be HPV DNA negative and 6 HPV DNA positive cases. Of the 6 cases; 5 were cancer of the cervix while one was carcinoma in situ. The HPV DNA positive cases was calculated to be 240% much lower than other series done elsewhere in Malaysia.